A fast and reliable method for monitoring of prophage‐activating chemicals. Issue 6 (12th January 2018) - Xu, Juan; Kiesel, Bärbel; Kallies, René; Jiang, Feng‐Lei; Liu, Yi; Maskow, Thomas
Summary: Bacteriophages, that is viruses that infect bacteria, either lyse bacteria directly or integrate their genome into the bacterial genome as so‐called prophages, where they remain at a silent state. Both phages and bacteria are able to survive in this state. However, prophages can be reactivated with the introduction of chemicals, followed by the release of a high number of phage particles, which could infect other bacteria, thus harming ecosystems by a viral bloom. The basics for a fast, automatable analytical method for the detection of prophage‐activating chemicals are developed and successfully tested here. The method exploits the differences in metabolic heat produced by Escherichia coli with (λ+) and without the lambda prophages (λ−). Since the metabolic heat primarily reflects opposing effects (i.e. the reduction of heat‐producing cells by lysis and enhanced heat production to deliver the energetic costs for the synthesis of phages), a systematic analysis of the influence of the different conditions (experimentally and in silico ) was performed and revealed anoxic conditions to be best suited. The main advantages of the suggested monitoring method are not only the possibility of obtaining fast results (after only few hours), but also the option for automation, the low workload (requires only few minutes) and the suitability of using commercially available instruments. The future challenge following this proof of principle is the development of thermal transducers which allow for the electronic subtraction of the λ+ from the λ‐ signal. Abstract : Bacteriophages in a silent state can be reactivated by anthropogenic chemicals, followed by the release of a high number of bacteriophages, which could infect related bacteria, thus harming ecosystems by a viral bloom. Inspired by this concern, a fast and reliable method for characterizing the prophage inducing properties of chemicals based on the metabolic heat was developed.